The Education of the National Character of Pancasila in Secondary School Based on Pesantren - Mukhamad Murdiono, M.Pd.; Miftahuddin Miftahuddin; Puji Wulandari Kuncorowati (Jurnal Cakrawala Pendidikan, 2017)
This study is aimed at describing (1) Pancasila-based character education in pesantren-based secondary schools, (2) the strategy employed by teachers in developing Pancasila-based character education, and (3) the obstacles faced by teachers in developing Pancasila-based character education. This research was descriptive in natureby employing qualitative approach. Research subjects were principals and teachers of Civic Education in several pesantren-based secondary schoolsin Yogyakarta Special Region. The data were collected through interviews, observation, and documentation. The collected data were analysed inductively.The results show that (1) the Pancasila-based character education is developed through the policy made by the principals and the teachers who developed the learning program, (2) the teacher’s strategy in developing Pancasila-based character educationis conducted by integrating intra and extracurricular programs, and (3) the obstacles faced by teachers in developing Pancasila-based character education are related to the fact that not all teachers are able to integrate Islamic values developed in pesantrento the values embodied in Pancasila in teaching and learning process. Keywords: character education, Pancasila, pesantren PENDIDIKAN KARAKTER KEBANGSAAN PANCASILA DI SEKOLAH MENENGAH PERTAMA BERBASIS PESANTREN Abstrak: Penelitian ini bertujuan untuk mendeskripsikan (1) pendidikan karakter kebangsaan Pancasila yang dikembangkan di sekolah menengah pertama berbasis pesantren; (2) strategi yang dilakukan guru dalam mengembangkan pendidikan karakter kebangsaan Pancasila; dan (3) kendala yang dihadapi guru dalam pengembangan pendidikan karakter kebangsaan Pancasila. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif.Subjek penelitian adalah kepala sekolah dan guru Pendidikan Kewarganegaraan di beberapa sekolah menengah pertama berbasis pesantren di Daerah Istimewa Yogyakarta.Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi.Teknik analisis data menggunakan analisis induktif. Hasil penelitian menunjukkan (1) pendidikan karakter kebangsaan Pancasila di sekolah dikembangkan melalui kebijakan yang dibuat kepala sekolah dan program pembelajaran yang dikembangkan guru; (2) strategi yang dilakukan guru dalam pengembangan karakter kebangsaan Pancasila melalui integrasi dalam program intra dan ekstrakurikuler; dan (3) kendala yang dihadapi guru dalam pengembangan pendidikan karakter kebangsaan yaitu belum semua guru mampu mengintegrasikan nilai-nilai keislaman yang dikembangkan di pesantren dengan nilai-nilai Pancasila dalam pembelajaran. Kata Kunci: pendidikan karakter, kebangsaan, Pancasila, pesantren